Mediating influence of crime type on victim satisfaction with police services: A comparative analysis across victims of property crimes and violent crimes in India - Kumar, TK Vinod (International review of victimology, 2018)
Different crimes have their own unique characteristics. Victim needs and experiences vary across crime types. However, there has been a tendency for the criminal justice system to treat victims as a homogeneous entity and respond to victims of different types of crimes in a routine manner. This is especially true in a developing country like India. This study, using victim survey data from India, examines whether the crime type (property crime or violent crime) has a mediating influence on the relation between the quality of procedure and outcome of police response on the one hand, and victim satisfaction on the other. The study concludes that the type of crime has a mediating effect on the relation between interpersonal justice, information justice and outcome, and the satisfaction of victims with services provided by the police.